APLIKASI KAFALAH DI BANK SYARIAH MANDIRI CABANG SURABAYA - Agus Slamet Seroji (Maliyah : Jurnal Hukum Bisnis Islam, 2013)
The majority of Islamic banking products, it is actually a blend of conventional banking practices with the basic principles of economic transactions Isla>m. However, with his eloquence, Islamic banking products to be very extensive and complete than conventional products, one product is Shari'ah banking services kafa>lah (bank guarantee). Application warranty services at Bank Syariah Mandiri Surabaya branch using contract kafa>lah wadi'ah was included in the financing and banking as the same as the level of risk financing and for-profit alike. Basically the bank guarantee is allowed in Isla> m, while the contract is used in accordance with the operation performed, the application of which occurred in Bank Syariah Mandiri make contract kafa>lah and wadi'ah was and is an agreement in principle tabarru '(goodness) converted into contract tijarah (business) by placing kafa>lah was to find and take advantage of wages that exceed the mere replacement of the administrative costs. In accordance with the agreement of the scholars that it should not change the contract because a contract tabarru tijarah (business).